First-Year Students and the Framework: Using Topic Modeling to Analyze Student Understanding of the Framework for Information Literacy for Higher Education - Harden, Melissa (Evidence Based Library and Information Practice, 2019)
Objective – The Framework for Information Literacy for Higher Education has generated a significant amount of discussion among academic librarians; however, few have discussed the potential impact on learning when students interact directly with the Framework itself. At the University of Notre Dame, over 1,900 first-year students completed an information literacy assignment in their required first-year experience course. Students read a condensed version of the Framework, then wrote a response discussing how a frame of their choosing was reflected in an assigned reading. The goal of this exploratory study was to determine if the students demonstrated an understanding of the themes and concepts in the Framework based on this assignment.Methods – Topic modeling, a method for discovering topics contained in a corpus of text, was used to explore the themes that emerged in the students’ responses to this assignment and assess the degree to which they connect to frames in the Framework. The model receives no information about the Framework prior to the analysis; it only uses the students’ words to form topics.Results – The responses formed several topics that are recognizable as related to the frames from the Framework, suggesting that students were able to engage effectively and meaningfully with the language of the Framework. Because the topic model does not know anything about the Framework, the fact that the responses formed topics that are recognizable as frames suggests that students internalized the concepts in the Framework well enough to express them in their own writing.Conclusion – This research provides insight regarding the impact that the Framework may have on student understanding of information literacy concepts.